Hello happy taxpayers no 8 - Frankyboots; Tjoyas, Alexios 1965-; Lévy-Hadida, Frédéric 1963-; Duchnock, Margot; Bolino, Pakito 1966-; Valium, Henriette 1959-2021; Caramel; Naylor, Pat; Burns; Ruijters, Marcel 1966-; Kamagurka 1956-; Krogold (H.H.T., 1989)
Record reviews, interview with Henry Rollins, cinema reviews, Une Saison Au Paradis (article about hardcore punk), text "Mon Beau Cygne" by Anette Berr, interview with Naked Raygun, Vomir Des Yeux (reviews of independent comics zines), interview with Steve Albini, text "Nus Sous Les Condoleances", interview with Ikue Mori, Susan Catherine comics, Vous Etes Ici poetry, article "Raconteurs D'Histoires", dossier RRR Records, The Ex: Aural Guerrilla, article on Jean-Luis Costes, cassettes reviews... + Vinyl 7inch with Smersh, Naked Raygun, A.C. Temple, Blackhouse, Black Jack
Offsetdruck. - Umschlag: farbig
Keywords: Graphzine